Associations between sarcopenia (defined by low muscle mass), inflammatory markers, and all-cause mortality in older adults: mediation analyses in a large U.S. NHANES community sample, 1999–2006 - Liu, Jia; Zhang, Fuchun (Frontiers in Medicine, 2025)
BackgroundSarcopenia is linked to increased mortality, but the specific role of inflammation in sarcopenia-related mortality remains poorly understood. This study aims to integrate various inflammatory biomarkers to develop an inflammation prognostic score (IPS) within the large, representative NHANES cohort. It also explores the association between sarcopenia, inflammatory markers, and mortality, and investigates whether inflammation mediates this relationship.MethodsThis study analyzed data from NHANES (1999–2006) on 3,544 participants aged 65 and older, with mortality follow-up through December 31, 2019, using death records from the National Death Index (NDI). Statistical analyses accounted for complex survey design and multiple imputation for missing data. Sarcopenia was defined using appendicular skeletal mass (ASM) adjusted for body mass index (BMI). Cox regression assessed the association between sarcopenia, inflammatory markers, and all-cause mortality. The IPS was developed using LASSO regression, and mediation analysis was conducted to assess whether inflammatory markers mediate the relationship between sarcopenia and mortality.ResultsAmong 3,544 elderly participants, sarcopenia was present in 25.4%, with a 66.6% overall mortality rate during the follow-up period. Multivariate Cox regression confirmed that sarcopenia is an independent risk factor for mortality [Hazard ratio (HR) = 1.235–1.281, P < 0.001]. Inflammatory markers were significantly associated with all-cause mortality. The IPS showed a clear trend of increasing mortality risk across quartiles, with HR reaching 2.044 in Q4 (P < 0.001). Mediation analysis showed that IPS mediated 20.8% of the relationship between sarcopenia and mortality, with the mediating effect remaining significant after adjusting for confounders.ConclusionThis study confirms the association between sarcopenia and increased mortality risk, with inflammation as a key mediating factor, highlighting its role in sarcopenia-related mortality.